THE IMPORTANCE AND RELEVANCE OF STUDENTS ' ECO-AESTHETIC COMPETENCE FOR TODAY (Academia Science Repository, 2023)
This article analyzes the importance and relevance of the development and formation of eco-aesthetic education in students, the role of pedagogues in this process, what exactly is the concept of eco-aesthetic education. The author examines the impact of environmental problems on the world community or, on the contrary, the positive and negative effects of humanity on the environment.